Public Speaking Skills in the Management of Psychosocial Maturity - Purwadini, Aminah; Nisa, Lutfi Firda; Lestari, Aghnia Dian (PT FORMOSA CENDEKIA GLOBAL, 2024)
Students as agents of change who will enter the industrial world are expected not only to master public speaking techniques but also to strengthen psychosocial aspects in managing emotions, building trust, and conveying information effectively. This study aims to reveal that public speaking skills play a role in the management of psychosocial maturity, the validity of data using triangulation techniques using qualitative research designs. The results of the study show that in terms of ethos, careful preparation can increase the credibility and clarity of the message conveyed by the speaker. In terms of pathos, the ability to manage emotions can reduce tension and maintain focus when speaking. Logos can increase trust by using evidence-backed arguments.